2018
DOI: 10.1371/journal.pone.0202677
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin mediates polyamine metabolism and sensitizes gastrointestinal cancer cells to antitumor polyamine-targeted therapies

Abstract: Curcumin, a natural polyphenol that contributes to the flavor and yellow pigment of the spice turmeric, is known for its antioxidant, anti-inflammatory, and anticarcinogenic properties. Capable of affecting the initiation, promotion, and progression of carcinogenesis through multiple mechanisms, curcumin has potential utility for both chemoprevention and chemotherapy. Previous studies demonstrated that curcumin can inhibit ornithine decarboxylase (ODC) activity in human leukemia and breast cancer cells, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 57 publications
(64 reference statements)
0
21
0
Order By: Relevance
“…In certain cancer cell types, cytotoxicity from these analogues is attributed to the production of H 2 O 2 via SMOX simultaneously with depletion of the natural PAs (50,121,122). Curcumin, a natural polyphenol and popular dietary supplement, was recently shown to increase uptake of these PA analogues, resulting in enhanced polyamine depletion and growth inhibition and allowing a substantial reduction in the required effective analogue dose (123). As curcumin possesses multiple antitumor properties, this combination with a PA analogue would target multiple anticancer pathways (124).…”
Section: Therapeutic Induction Of Polyamine Oxidationmentioning
confidence: 99%
“…In certain cancer cell types, cytotoxicity from these analogues is attributed to the production of H 2 O 2 via SMOX simultaneously with depletion of the natural PAs (50,121,122). Curcumin, a natural polyphenol and popular dietary supplement, was recently shown to increase uptake of these PA analogues, resulting in enhanced polyamine depletion and growth inhibition and allowing a substantial reduction in the required effective analogue dose (123). As curcumin possesses multiple antitumor properties, this combination with a PA analogue would target multiple anticancer pathways (124).…”
Section: Therapeutic Induction Of Polyamine Oxidationmentioning
confidence: 99%
“…Curcuminoids are natural phenylpropanoids extracted from the plant Curcuma longa that have innumerous therapeutic properties including antioxidant (Wang et al, 2019), antiinflammatory (Dai et al, 2018), anticancer (Murray-Stewart et al, 2018;Ravindranathan et al, 2018), and cholesterollowering (Ferguson et al, 2018). They have also been reported as protective agents for several neurodegenerative diseases (Maiti and Dunbar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] The studies have found that curcumin inhibits cell proliferation and induces apoptosis in several tumors. [22][23][24][25] Besides, curcumin has been reported to enhance autophagy-related cell death, 26 and induce cell apoptosis through lysosomal membrane permeabilization-medicated autophagy or downregulating lncRNA. 27,28 What's more, curcumin exerts protective effects through promoting autophagy and ameliorating apoptosis in diabetic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%